Analysis of Implications in Interpersonal Communication on Badarawuhi Figures in Dancer Village - Lutfia, Nabila Shauma (Ridwan Institute, 2025)
This study examines the implications in interpersonal communication used by the character Badarawuhi in Desa Penari, focusing on how implied meanings function to manipulate and control other characters. The research highlights how Badarawuhi’s speech, though seemingly benign, carries manipulative undertones through seduction, emotional coercion, and veiled threats. The study aims to: (1) identify the types of implications in Badarawuhi’s speech, (2) analyze their alignment with or violation of Grice’s maxims, and (3) explore how social relationships influence the interpretation of these implications. Using a qualitative descriptive method, the research analyzes dialogues from Desa Penari, applying pragmatic content analysis to uncover hidden meanings. Findings reveal that Badarawuhi strategically violates conversational maxims to exert psychological control, often disguising commands as polite requests or rhetorical questions. For instance, phrases like “Would you like to see your mother here?” imply emotional blackmail, leveraging familial bonds to pressure compliance. The study concludes that Badarawuhi’s speech reflects the cunning nature of mythological snake figures, using subtle language to dominate victims without overt aggression. These findings contribute to pragmatic studies by demonstrating how implications serve as tools of manipulation in hierarchical relationships, with practical applications for understanding power dynamics in communication.